Tatalaksana Skizofrenia Pada Kehamilan: Laporan Kasus - Junita Indarti; Dwiana Ocviyanti; Erda Ayu Umami (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Schizophrenia is a severe mental disorder, characterized by deep thinking disturbances, affecting language, perception, and sense of self. This often includes psychotic experiences, such as hearing sounds or delusions. The most common age of onset for schizophrenia in women is from ages 25-35 (reproductive age). We report a case of a 27-year-old woman with pregnancy and schizophrenia paranoid. Reproductive age women with schizophrenia need comprehensive management during their reproductive years, including contraception, prenatal care, antenatal care, postnatal care, as well as safe and effective parenting.